Carbon quantum dots-stabilized Pickering emulsion to prepare NIR light-responsive PLGA drug delivery system. (June 2020) - Zhou, Tongchang; Huang, Zheng; Wan, Feng; Sun, Yi
Graphical abstract: A new strategy to prepare NIR light-responsive PLGA drug delivery systems via carbon quantum dots-stabilized Pickering emulsion polymerization was developed. PLGA was dissolved in DCM as oil phase. RCDs were dispersed in water in single emulsion while they were dispersed in DCM in double emulsion. Abstract: A new strategy to prepare NIR light-responsive Poly-lactide-co-glycolide (PLGA) drug delivery systems via carbon quantum dots-stabilized Pickering emulsion polymerization was developed. We successfully fabricated oil-in-water single emulsion and water-in-oil-in-water double emulsion for loading hydrophobic and hydrophilic drugs, respectively.